The Structural Neural Substrates of Persistent Negative Symptoms in First-Episode of Non-Affective Psychosis: A Voxel-Based Morphometry Study - Benoit, Audrey; Bodnar, Michael; Malla, Ashok; Joober, Ridha; Lepage, Martin (Frontiers in Psychiatry, 2012)
Objectives: An important subset of patients with schizophrenia present clinically significant persistent negative symptoms (PNS). Identifying the neural substrates of PNS could help improve our understanding and treatment of these symptoms. Methods: This study included 64 non-affective first-episode of psychosis (FEP) patients and 60 healthy controls; 16 patients displayed PNS (i.e., at least 1 primary negative symptom at moderate or worse severity sustained for at least 6 consecutive months). Using voxel-based morphometry (VBM), we explored for grey matter differences between PNS and non-PNS patients; patient groups were also compared to controls. All comparisons were performed at p<0.05, corrected for multiple comparisons. Results: PNS patients had smaller grey matter in the right frontal medial-orbital gyrus (extending into the inferior frontal gyrus) and right parahippocampal gyrus (extending into the fusiform gyrus) compared to non-PNS patients. Compared to controls, PNS patients had smaller grey matter in the right parahippocampal gyrus (extending into the fusiform gyrus and superior temporal gyrus); non-PNS patients showed no significant differences to controls. Conclusions: Neural substrates of persistent negative symptoms are evident in FEP patients. A better understanding of the neural etiology of PNS may encourage the search for new medications and/or alternative treatments to better help those affected.